Implementation of Digital Presence in Enforcing Employee Work Discipline at Perumdam Tirta Waesai Barru - Naufal Nisphu Ramadhan; Sirajuddin Saleh; Hasyim, Nasaruddin (Pinisi Journal of Officers Review, 2025)
The digital attendance system in enforcing employee work discipline at Perumdam Tirta Waesai Barru offers an effective solution to disciplinary and fraud problems that often occur in manual systems, with benefits such as increased transparency, administrative efficiency, and support for employee performance. This study aims to determine the implementation of digital attendance in enforcing employee work discipline at Perumdam Tirta Waesai Barru. The research is qualitative, using data collection techniques through observation, interviews and documentation. The results of this study indicate that the implementation of digital attendance in enforcing employee work discipline at Perumdam Tirta Waesai Barru is running "well". This is shown in the communication indicator, the implementation of digital attendance, such as fingerprints, has improved employee work discipline by making it easier to track employee attendance and can help manage employee attendance more safely and efficiently, such as avoiding unauthorized access or data manipulation. Resource indicators, employees support the implementation of digital attendance to enforce work discipline because digital attendance provides accurate attendance records and cannot be manipulated. Disposition indicators, employee attitudes towards the implementation of digital presence are very positive and support and agree with the implementation of digital presence. Bureaucratic structure indicators show that digital presence implementation can significantly improve time efficiency and employee discipline, leading to a better work environment and discipline. Effective digital presence implementation can be achieved by following the rules (SOPs) and policy mechanisms for digital presence implementation.